2017
DOI: 10.1080/19768354.2017.1382388
|View full text |Cite
|
Sign up to set email alerts
|

Functional gene networks based on the gene neighborhood in metagenomes

Abstract: The gene neighborhood in prokaryotic genomes has been effectively utilized in inferring cofunctional networks in various organisms. Previously, such genomic context information has been sought among completely assembled prokaryotic genomes. Here, we present a method to infer functional gene networks according to the gene neighborhood in metagenome contigs, which are incompletely assembled genomic fragments. Given that the amount of metagenome sequence data has now surpassed that of completely assembled prokary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Thus, we generated two functional networks using probability- and distance-based measures of gene neighborhood. We also found that distance-based gene neighborhoods across metagenomes correlated with functional associations (32). We could infer two functional networks by gene neighborhood analysis using 754 human microbiomes (27) and 242 ocean metagenomes (28).…”
Section: Network Database Improvementmentioning
confidence: 79%
“…Thus, we generated two functional networks using probability- and distance-based measures of gene neighborhood. We also found that distance-based gene neighborhoods across metagenomes correlated with functional associations (32). We could infer two functional networks by gene neighborhood analysis using 754 human microbiomes (27) and 242 ocean metagenomes (28).…”
Section: Network Database Improvementmentioning
confidence: 79%
“…It has been proposed that proteins that are functionally related tend to be encoded in close proximity to each other on the genome (31)(32)(33)(34)(35). Identifying genes in the neighborhood of the gene of interest that are conserved across various species can be a helpful inference of potential physical interactions and functional relationships among them (31)(32)(33)(34)(35). To identify a potential interacting partner of PrbP Las , the genomic context of prbP Las was examined using the Joint Genome Institute (JGI) IMG genome viewer and SEED (Markowitz et al [36]).…”
Section: Resultsmentioning
confidence: 99%
“…We inferred cofunctional links based on the gene neighborhood across the 1,747 archaeal and bacterial genomes with two complementary measures of gene neighborhood: distance-based measures and probability-based measures (18). In addition, a metagenome-based gene neighborhood method (38) was used for KlebNet. We utilized contig sequences from the Human Microbiome Project (39) and TARA Ocean Project (40).…”
Section: Methodsmentioning
confidence: 99%